The use of epinephrine in out-of-hospital cardiac arrest: a retrospective study of the effects of administration timing and cumulative doses on outcome in a physician-staffed emergency medical service system - Grübl, Tobias; Jungblut, Janine; Rupp, Dennis; Ha, Chung Shing Rex; Ploeger, Birgit; Haag, Dana Maresa; Uzun, Davut D.; Jaenig, Christoph Walter; Sassen, Martin Christian; Schieffer, Bernhard; Timmermann, Lars; Betz, Susanne (BMC emergency medicine, 2025)
Background Epinephrine administration during cardiopulmonary resuscitation (CPR) has been a long-standing recommendation, but the evidence is controversial. This study investigated effects of epinephrine administration in a physician-staffed emergency medical service (EMS) system and for the first time addressed the quality of chest compressions.Methods Complete datasets of adult patients who suffered out-of-hospital cardiac arrest (OHCA) and received CPR were retrospectively analysed. Factors (time of collapse, bystander CPR, EMS arrival, initial cardiac rhythm, suspected cause of OHCA, and for the first time also quality of chest compressions) that may influence outcome (return of spontaneous circulation [ROSC], survival to discharge, neurological status) and epinephrine administration (time of first administration, total dose, route of administration) were analysed after adjustment. Results A total of 1141 patients were identified; 1090 patients were included. Patient data (age, gender, pre-existing conditions, initial electrocardiographic rhythm, suspected cause) were comparable to those reported in international studies. Mean chest compression depth was 5.5 cm (SD: 0.8 cm). Median compression rate was 115/min (SD: 12/min). The first epinephrine dose was administered after a mean period of 6:43 min after EMS arrival (SD: 9:30 min) and 18:23 min after collapse (SD: 11:13 min). Earlier epinephrine administration was associated with increased rates of ROSC and survival to discharge. Patients who achieved ROSC and survived to discharge received less than 6 mg of epinephrine. Early administration was associated with improved outcomes, especially in patients with asystole. Neurological outcomes, however, deteriorated with increasing epinephrine doses. Conclusions This study supports the benefit of early administration of limited doses of epinephrine in OHCA patients. Higher epinephrine doses may be associated with poorer outcomes. Further randomised controlled studiesthat investigate the administration of medications within fifteen minutes after collapse and also address the quality of basic life support measures are required to assess the actual benefits of epinephrine during CPR.